The Application of Portfolio-Based Assessments to Improve Students’ Probleum Solving - Supriatna, Encep (Universitas Pendidikan Indonesia, 2018)
One of the objectives of Social Studies as Improve Citizenship transmission, and studying as reflevtive inquiry, developing student behavior, and the primary purposes of social studies to help young people develop the ability to make informed and reasoned decision for public good citicens of culturally diverse, (NCSS, 1994).. Another approach that can be used by lecturer is giving assignment or project to students. From the product that produced by the students and their appearance in the classroom, it can be seen which group the process of making the product involves all members of the group and not involves all members of the group. One of the social skill in social studies which can be developed in the lecture process is by using portfolio-based assessment that can vary in form, one of the advantage of a portfolio assessment is the lecturer can assess the students’ overall abilities. On lectures of social studies, lecturer assigns students to make educational props for basic education in accordance with predetermined theme. After finishing the product, every group is asked to present their work to be commented by other groups, while using portfolio assesment the student can reflective inquiry many values and using it’s for decision making for the public policy